Influence of place of birth and gender on the health component of the quality of life of students - O.J. Andriichuk; O.Z. Kasarda (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: to analyze indicators of physical and mental health components in quality of life of students according to gender and place of birth. Material : the study involved 513 students aged 17 - 22 years old. Depending on the place of birth of the students were grouped into 5 groups: residents of large cities, small cities, towns, and villages; sat. Results : the highest rate of physical activity in girls (91.75 points) and men (94.9 points) of the major cities. The lowest rates are indicator role activities (47.86 points) girls from small towns, vitality index (57.25 points) in men hail from towns. The correlation coefficients between the indicators of quality of life of students: high rates of mental health component in comparison with the physical component. Conclusions : it was found that students regardless of sex, physical health component above the psychological component. Gender difference between physical health component is greater among residents of the town. In terms of mental health component of the residents of small towns.